IDENTIFICATION OF EXTERNAL STAKEHOLDERS OF OIL AND GAS COMPANIES: KEY FACTORS - Okhotnikov, Andrii (Current Problems of Sustainable Development, 2026)
The article analyzes the process of identifying external stakeholders of oil and gas companies in Ukraine. It is emphasized that the oil and gas sector occupies a special place in the structure of the modern global economy. Its key characteristic is the intertwining of purely economic, political, and social interests of individuals, corporations, and nation-states. This significantly broadens the range of potential external stakeholders and complicates the process of their identification. For Ukraine, the functioning of oil and gas companies is of critical importance, particularly given the country’s dependence on imports of petroleum products. The initial research hypothesis was that the key factors shaping the set of external stakeholders of oil and gas companies are: the controversial nature of geographic factors related to reserve locations, as well as oil and gas supply and demand; the specifics of competitive mechanisms in the global economy; the role of the state as regulator and owner; the characteristics of the production process in the industry; the significant non-economic influence of the sector; and the paradigm of the “green” economy and its spread. Each identified factor was examined in terms of its impact on the formation of the external stakeholder set. It is argued that the non-economic role of the oil and gas sector is most clearly manifested during periods of oil crises. Competitive mechanisms in the oil, gas, and refined products markets are based on both price and non-price factors. The complexity and heterogeneity of the oil and gas complex, as well as the logical interconnectedness of its components, significantly complicate stakeholder identification for each specific company. The dual role of the state – as both regulator and owner – against the backdrop of the sector’s significant importance for a country’s economic and social development, makes the state one of the key stakeholders for oil and gas companies. “Green” trends are an important factor that oil and gas companies must consider when engaging with stakeholders. An important scientific task at the current stage is the development of methodological approaches to identifying external stakeholders of oil and gas sector companies, which should subsequently be used to improve management tools in this area.
Keywords: stakeholders; external stakeholders; economic interest of the stakeholders; oil and gas complex; enterprises of oil and gas complex; oil; gas